KONSEP ADIL POLIGAMI DALAM Q.S AN-NISA: 129 - Erma Sauva Asvia (Institut Agama Islam Darul Ulum Kandangan, 2020)
Polygamy has a condition in terms of justice. Something that can often not be realized by husbands who do polygamy. In Q.S. An-Nisa verse 129 the justice referred to is in terms of feelings of affection and love, husbands should not have mutual respect for each other. However, in the phenomenon of polygamy these things are very difficult to realize, the justice applied so far is in terms of giving the same nominal amount, the division of a balanced turn between each other and according to the husbands it has been considered a justice even though according to the wives in terms of compassion and love has not materialized only by equal division, because compassion and love is something that is difficult to divide equally